Illegal Cigarette Profits and Informal Accounting Practices: A Political Economy of Accounting Perspective - Assri Nuur Tri Oktafiyanti; Bambang Haryadi; Robiatul Auliyah (Politeknik Ganesha Medan, 2025)
This study examines the phenomenon of illegal profits from the sale of cigarettes without excise stamps in GBG-SLM Regency using the Political Economy of Accounting (PEA) approach. The main objective is to analyze the practice of illegal cigarette profits from a PEA perspective and highlight its implications for the economic system and fiscal regulation at the local level. The research employed a qualitative method with a critical paradigm, where data were collected through field observations, in-depth interviews with business actors, and documentation analysis related to production and distribution activities. The findings reveal that the illegal cigarette industry is dominated by small and medium-sized kinship-based enterprises. The profits generated are relatively high but remain unrecorded in the formal financial system, creating gaps in state revenue. Accounting practices used by the actors serve merely as a formality to evade fiscal obligations, rather than as tools for transparency or accountability. This condition reflects the interplay of power relations, local culture, and economic interests in sustaining the practice of illegal cigarette trade.The novelty of this research lies in its PEA-based analysis that integrates political economy perspectives with local values and culture, thereby contributing to the formulation of more contextual fiscal policies. Thus, this study emphasizes that accounting is not solely a technical instrument but also a social, political, and cultural practice that shapes the sustainability of public policy.